Trans-generational immune priming against American Foulbrood does not affect the performance of honeybee colonies - Leponiemi, Matti; Wirta, Helena; Freitak, Dalial (Frontiers in Veterinary Science, 2023)
Honeybees are major pollinators for our food crops, yet they face many stressors all over the world. One of the major threats to honeybee health are bacterial diseases, the most severe of which is the American Foulbrood (AFB). Recently a trans-generational vaccination approach against AFB has been proposed, showing strong potential in protecting the colonies from AFB outbreaks. Yet, what remains unstudied is whether the priming of the colony has any undesired side-effects. It is widely accepted, that immune function is often a trade-off against other life-history traits, hence priming a colony with AFB could have an effect on the colony performance. In this experiment we set up 48 hives, half of them with primed queens and half of them as controls. The hives were placed in six apiaries, located as pair of apiaries in three regions. Through a two-year study we monitored the hives and measured their health and performance. We measured hive weight, frame contents such as brood amount, worker numbers, and honey yield. We studied the prevalence of the most common honeybee pathogens in the hives and relevant immune genes in the offspring at larval stage. No effect of trans-generational immune priming on any of the hive parameters was found, suggesting that exploiting the trans-generational priming could serve as a safe tool in fighting the AFB in apiaries. Yet we did find other factors contributing on various hive performance parameters. Interestingly not only time but also the region, although only ten kilometers apart from each other, had an effect on the performance and health of the colonies, suggesting that the local environment plays an important role in hive performance.